PERANCANGAN APLIKASI FORM PELAYANAN JASA PADA STUDIO FOTO PRODUK UNIK BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE - Fitriani, Desi; Risah Subariah (Jurnal Publikasi Teknik Informatika, 2022)
Studio Photo Productis Unik a Photo Studio located in the South Tangerang city area. This Unique Product Photo is one of the places that provides many types of services according to the wishes of customers in the field of photography. In this photo studio, the bookkeeping system has not utilized one application using only Google spreadsheets, so it takes quite a long time in the reporting process. Developments in the field of photography have developed rapidly and are relatively broad, starting from technology and also visually. This research aims to help the problems that exist in the Unique Product Photo Studio by realizing an application design on the web-based Unique Product Photo Studio using the prototype method in the service process. The system development method uses the prototype method, for testing techniques using black box and white box. The equipment used to build this system uses the Visual Studio Code application for the text editor, MySQL to design the database and Bootstrap as the website framework. photos, galleries and also make photo orders.